The effects of axial loading on the morphometric and T2 characteristics of lumbar discs in relation to disc degeneration. (March 2021) - Abdollah, Vahid; Parent, Eric C.; Su, Alex; Wachowicz, Keith; Battié, Michele C.
Abstract: Background: Intervertebral disc degeneration affects the morphology, biomechanics and biochemistry of the disc. The study aimed to compare the effects of compression and traction on lumbar discs measurements in relation to degeneration. Methods: Thirty-five volunteers (30 (SD 11) yrs.) with and without chronic back pain rested supine 15 min before an unloaded T2 -mapping MRI, were then loaded 20 min with 50% body weight with imaging during the last 5 min, and then repeated this process under traction. For lumbar discs, height, angle, width, mean-T2, and T2 -weighted centroid locations were calculated. A repeated measure ANCOVA and Cohen's d compared loading conditions. Relations between measurement changes between conditions and degeneration assessed by Pfirrmann ratings were examined graphically. Findings: From compression to traction, we observed significant: decrease in L1–2 mean-T2 (Effect size = −0.35); inferior and posterior shift in L4–5 (0.4, 0.14) and L5-S1 (0.25, 0.33) T2 -weighted centroid. From unloaded to compression, we observed a significant: increase in L5-S1 width (Effect Size = 0.22); anterior shift in L1–2 T2 -weighted centroid (0.39); and L3–4 (mean 2.1°) and L4–5 (1.8°) extension angle. More degeneration was graphically related with larger changes from Compression to Traction (more superior and, anterior position of the T2 -weighted centroid, increased height, reduced extension of segmental angle) and from Unloaded to Compression larger c hanges in inferior displacement of the T2 − weighted centroid, decrease in height) but less anterior displacement of the centroid and less change in segmental angles. Interpretation: The largest loading responses were at lower levels, generally with more degeneration. T2 -weighted centroid locations, angle and disc height detected the largest loading response. Graphical abstract: Unlabelled Image Highlights: Effects of disc compression and traction measured using geometric and T2 centroids. The largest responses to loading were observed at the lower lumbar levels. The magnitude of responses to loading were associated with severity of disc degeneration. T2 disc centroid, disc angle and height best detect the effects of loading. Biomarkers hold promise as objective measurements of degeneration.